2022
DOI: 10.1089/whr.2021.0153
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Body Mass Index and Cancer Screening Adherence Among Latinas in the United States and Puerto Rico

Abstract: Background: Research on the role of body size on cancer screening is mixed with few studies among Latinas in the United States. We evaluated the association between body size and cancer screening adherence among Latinas living in Puerto Rico and the rest of the United States. Methods: We conducted a cross-sectional study using 2012–2018 Behavioral Risk Factor Surveillance System data among Latinas 50–64 years of age ( n = 16,410). Breast, cerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
0
0
0
Order By: Relevance
“…Identifying CRC at an early stage through screening is crucial not only to improve CRC outcomes but also to manage other chronic conditions, which could ultimately improve relevant clinical outcomes (15). Previous studies examined the relationship between the presence of chronic conditions (eg, diabetes, cardiovascular disease, obesity) and CRC screening, but results were inconsistent (16)(17)(18)(19)(20). Some studies showed that chronic conditions were associated with lower rates of screening, while others found higher rates (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Identifying CRC at an early stage through screening is crucial not only to improve CRC outcomes but also to manage other chronic conditions, which could ultimately improve relevant clinical outcomes (15). Previous studies examined the relationship between the presence of chronic conditions (eg, diabetes, cardiovascular disease, obesity) and CRC screening, but results were inconsistent (16)(17)(18)(19)(20). Some studies showed that chronic conditions were associated with lower rates of screening, while others found higher rates (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies examined the relationship between the presence of chronic conditions (eg, diabetes, cardiovascular disease, obesity) and CRC screening, but results were inconsistent (16)(17)(18)(19)(20). Some studies showed that chronic conditions were associated with lower rates of screening, while others found higher rates (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%